The Analysis of Factors Related to The Implementation of The COVID-19 Health Protocol For Cadets at Malahayati Merchant Marine Polytechnic of Aceh in 2021 - Elly Kartika Farida; Said Usman; Sofia Sofia; Nurjannah Nurjannah; Irwan Saputra (Universitas STRADA Indonesia, 2021)
COVID-19 is a disease which prevention can be done with the 5M health protocol. The purpose of this study is to determine what factors are associated with the implementation of the COVID-19 health protocol. This research was conducted using a questionnaire with quantitative analytical methods and cross sectional approach. The population in this study were all cadets who were doing face-to-face learning on campus and had experienced face-to-face learning in the previous period. The questionnaire was tested for validity and was also declared reliable with a Cronbach alpha value of 0.673 which was tested on 35 samples. The results showed that there were two factors that had a significant relationship with the implementation of the COVID-19 health protocol, namely knowledge (p 0.00), attitude (p 0.03) and the results of multivariate analysis showed that the most dominant variable influenced the implementation of the COVID-19 health protocol is knowledge (ß = 19,536).